Development of community infrastructure through community forestry funds: what infrastructure gets priority? - Pokharel, RK (Banko Janakari, 2010)
Community forestry is a well established management form in Nepal. The success of community forestry in improving the forest condition encouraged the government to initiate some developmental works beyond the fulfillment of only basic forestry needs. This paper seeks to explore the investment made by CFUGs in community infrastructures and their priorities as well. Primary data from three mid-hill districts of Nepal were collected from questionnaire survey of 100 CFUGs. The results suggested that community infrastructure was the largest category of expenditures of CFUG funds wherein the majority of the CFUG accorded investment priority to schools. This paper concludes that higher CFUG income has led to a proportionately higher investment in community infrastructures and suggests that it was necessary to increase CFUG income to promote investment in community infrastructures. Investing CFUG funds on schools is a good harbinger of local development that contributes to the achievement of the Millennium Development Goal of universal primary education. Key words: CFUG; CFUG funds; community forestry; community infrastructures DOI: 10.3126/banko.v20i1.3508 Banko Janakari, Vol. 20, No. 1 pp.44-50